Ensayklopidiya ng pilosopiya - Quito, Emerita S. (Manila De La Salle University Press, 1993)
This encyclopedia is written in Filipino. It is divided into four parts: I. Dictionary- wherein English words are translated or explained in full details using the tagalog word. II. Bibliographies- it contained biographical information about the authors, their names, date of birth, date of death, place of origin, and the title of the book they wrote. III. Subject or Topic- where specific subjects were given full description. IV. Quotations. This includes all the familiar quotations given by the dictionary before going to the subject/topic. The encyclopedia is also concentrated more on Filipino philosophies. It has an Index.
Keywords: Philosophy -- Encylopedias